Experimental Study on Dynamic Compression Characteristics of Red Sandstone under Wetting-Drying Cycles - Bin Du; Haibo Bai; Minglei Zhai; Shixin He (Advances in Civil Engineering)
To study the influence of wetting-drying cycles on dynamic mechanical properties of rock masses, the impact compression tests of red sandstone samples were carried out by using a split Hopkinson pressure bar (SHPB) apparatus with a diameter of 50 mm. The results showed that under the same number of wetting-drying cycles, the dynamic compressive strength of red sandstone increased exponentially with the strain rate, and the sensitivity of the strain rate decreased with the increase of wetting-drying cycles. The deterioration effect of wetting-drying cycles was significant, and the dynamic and static compressive strength decreased with the increase of wetting-drying cycles; the higher the strain rate, the stronger the sensitivity to wetting-drying cycles. Besides, the influence of wetting-drying cycles and strain rate was comprehensively studied, and the equation of dynamic compressive strength of red sandstone was obtained. After different wetting-drying cycles, the fractal characteristics of red sandstone dynamic fragmentation were obvious, and the fractal dimension was 2.02–2.80, and the fractal dimension increased logarithmically with the strain rate. Finally, the internal microstructure of red sandstone after different wetting-drying cycles was analyzed, and the degradation mechanism of the rock by the cycles was discussed.